Improving Students' English Pronunciation Skills Through Audio-Visual Media - Heddy Heddy (International Journal of Educational Technology and Society, 2025)
Mastery of pronunciation skills is a crucial aspect in English oral communication. This study aims to describe the effectiveness of film and song-based audio-visual media in improving the pronunciation skills of English study program students. Using a descriptive qualitative approach with a case study design, data were obtained through observation, interviews, and documentation of pronunciation tests. The results showed that the integration of film and song media was able to significantly improve students' intelligibility, accuracy, and fluency. Films provide exposure to native speaker pronunciation in real contexts, while songs play a role in reducing anxiety and increasing self-confidence through sound repetition in a relaxed learning atmosphere. These findings are in line with recent studies that emphasize the importance of contextual and authentic media in teaching pronunciation. It is recommended that teachers utilize audio-visual media optimally in learning to create a more interesting and meaningful learning experience.